Analisis Pemanfaatan Aplikasi E-Ticketing Dengan Metode Technology Organization Environment (TOE) Framework - Ari Muhardono; Wenti Ayu Sunarjo; Rika Adriyana; Tarismha Winda Sari; Syarifatun Ni'mah (Jurnal Minfo Polgan, 2026)
The tourism industry is undergoing rapid transformation driven by digital technology adoption. E-ticketing systems have been widely implemented to improve operational efficiency and enhance visitor convenience. Tirta Arum Swimming Pool has adopted an e-ticketing application since 2024; however, its utilization remains suboptimal, as visitors continue to prefer on-site ticket purchases. This study investigates e-ticketing utilization from the management perspective using the Technology–Organization–Environment (TOE) framework. A qualitative case study approach was employed through in-depth interviews with ten managerial informants. Data were analyzed using thematic analysis supported by NVivo software, focusing on technological, organizational, and environmental dimensions. The findings indicate that the e-ticketing system is technologically reliable and user-friendly, contributing to improved operational efficiency, although further development is required in system integration and barcode validation. Organizational support and human resource readiness are strong, yet the absence of formal policies and standard operating procedures constrains optimal utilization. Environmentally, adequate infrastructure supports implementation, but limited promotion and entrenched visitor habits hinder the adoption of online ticketing features. Keywords: E-ticketing; TOE framework; tourism digitalization; qualitative study; management perspective